Implementasi Nilai Tat Twam Asi sebagai Upaya Penguatan Empati Siswa SDN 3 MENGWI - Kadek Lisda Agistia Wiharta Pratiwi; Dewa Bagus Sanjaya; I Nengah Suastika (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Strengthening empathy among elementary school students is an essential aspect of the educational process because the ability to understand, appreciate, and respond to the feelings of others influences the quality of students' social interactions. The increasingly complex social environment requires schools to focus not only on academic achievement but also on character development through moral values and local cultural wisdom. This study aims to describe the implementation of the Tat Twam Asi values as an effort to strengthen empathy among students at SDN 3 Mengwi. The study employed a qualitative descriptive approach involving the principal, classroom teachers, and students in Grades IV–VI as the research participants. Data were collected through observation, interviews, and documentation. Data were analyzed using the Miles, Huberman, and Saldana interactive model through the stages of data condensation, data presentation, and conclusion drawing. The findings indicate that the values of Tat Twam Asi were implemented through the habituation of mutual respect, helping classmates, collaborative learning, teacher role modeling, the integration of values into school activities, and positive conflict resolution. This implementation contributed to improving students' social awareness, tolerance, ability to understand others' perspectives, and empathetic behavior. The values of Tat Twam Asi can serve as a local wisdom-based approach that is relevant for strengthening character education in elementary schools.